Parasitosis y grado de anemia en gestantes atendidas en centros de salud de Iquitos, 2018 - Rimachi Quiroz, Ana Patricia (2023)
The main objective of this work was to determine the relationship between the presence of parasites and the degree of anemia in pregnant women treated in health centers in the city of Iquitos, this research had a non-experimental cross-sectional design, the sample considered was 423 pregnant women from a previous study from 3 health centers in the city of Iquitos: Bellavista Nanay Health Center, I-2 Progreso Health Post and Belén Health Center, the coproparasitological method used for the identification of parasites was Kato Katz. In the results obtained, a statistically significant relationship was found between the presence of anemia and the presence of the intestinal parasite Ancylostoma duodenale/American Necator (P=0.025), since more than 50% of pregnant women with A. duodenale/N. americanus infection anemia presentation. The percentage of anemia was higher in the group of pregnant women with at least one parasite, however, the difference was not statistically significant, this result could be due to the treatment for anemia that pregnant women receive during their control visits.